Identifying bonding interface flaws in CRTS III type ballastless track structure using the impact-echo method. (15th January 2021) - Jiang, Wei; Xie, Youjun; Wu, Jianxian; Guo, Jianguang; Long, Guangcheng
Highlights: Full-scale size field experiments of CRTS III type ballastless track structure. Factors influencing the experimental results of the impact-echo method. Apparent state of the bonding interface corresponds to the spectra of impact-echo method. Flaw identification function F(y) based on the spectra. Abstract: The bonding interface is a part of China Rail Track System III (CRTS III) type ballastless track structure that is prone to concealed flaws. The bonding interface is between the self-compacting concrete (SCC) filling layer and the steam-cured concrete precast plate. It is very important to detect the quality of the bonding interface. This paper investigates the feasibility of using the impact-echo method to detect the bonding interface flaws. The testing identification results of the bonding interface via the impact-echo method is compared with the actual quality state obtained by on-site uncovering plate. The main factors affecting the corresponding results are analyzed by field experiments. And the spectra of the impact-echo method under different flaw conditions are discussed. The relationship between the spectra and the actual flaws is analyzed in detail. A flaw identification function based on spectra is established to effectively identify bonding interface flaw types. This work will provide important technical supports for developing a reliable non-destructive testing method to inspect the bonding interface quality state.